RISK FACTORS FOR DIABETES MELLITUS IN MEN OF PRODUCTIVE AGE IN INDIA (NATIONAL FAMILY HEALTH SURVEY 2015-2016) - Maya Fernandya Siahaan; Trias Mahmudiono; Mahmudah Mahmudah; Soenarnatalina Melaniani; Syahfitri Wulandari (Universitas Airlangga, 2023)
Diabetes Mellitus (DM) is a serious health problem that continues to increase and can cause morbidity and mortality in many countries. India as a country with the second highest number of DM cases in the world after China has around 77 million cases in adults aged 20-79 years and is estimated to increase by 134 million in 2045. The cause of the incidence of DM in adults is multifactorial. The purpose of this study was to determine and analyze the risk factors associated with the incidence of DM in adults aged 15-49 years in India. This quantitative study uses a cross-sectional approach. This research data source was secondary data from the 2015-2016 National Family Health Survey (NHFS-4). The study sample size was a male adult population aged 15-49 years in 157 rural and urban areas in India. The independent variables studied were age, meat consumption, alcohol consumption, fried food consumption, smoking, economic status, education level, place of residence, and employment status, while the dependent variable is the incidence of DM. The results from the chi-square show that there were relationships between age, meat consumption, alcohol consumption, fried food consumption, smoking, economic status, education level, place of residence, and the incidence of DM in adult men aged 15-49 years in India. The results of the logistic regression test showed that age, smoking habits, and economic status had a significant effect. Meanwhile, the most influential factor was the higher economic status with an OR of 0.628 times higher having type 2 diabetes.